Modified diaphragm, preparation method and lithium metal battery
By using a modified separator in a lithium metal battery, combining a composite material of carboxylated precursor and carbon nanotubes, the problems of lithium dendrites growth and interface side reactions are solved, and the cycle stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202411786448.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The uncontrollable growth and interface side reaction of lithium dendrites in lithium metal batteries lead to problems of cyclic stability and safety, and existing inhibitory strategies are difficult to balance the uniformity and efficiency of lithium deposition.
Using a modified separator, including a base film and a modified coating, the coating consists of a carboxylation precursor and a carbon nanotube composite material, increases the electrolyte wetting and hydrogen bonding through carboxylic functional groups to inhibit lithium dendrites growth, and passes carbon The nanotubes provide additional lithium ion transport channels to form a protective SEI film.
It improves the electrochemical performance of lithium metal negative electrode, enhances lithium ion transport and conductivity, inhibits lithium dendrites' growth and interface side reactions, and extends the cycle life and safety of the battery.
Smart Images

Figure CN119253196A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a modified diaphragm, a preparation method and a lithium metal battery. Background Art
[0002] With the growing global demand for clean energy and portable electronic devices, the development of energy storage systems with high energy density, long cycle life and high safety has become a research hotspot. Lithium metal batteries are regarded as an important candidate for the next generation of energy storage technology because their theoretical specific capacity (3860 mAh / g) is much higher than that of traditional graphite anodes (372 mAh / g). However, the application of lithium metal anodes faces major challenges, especially the uncontrollable growth of lithium dendrites, which not only limits the cycle stability and safety of the battery, but also may cause internal short circuits, which can cause thermal runaway or even explosion in severe cases.
[0003] Although existing strategies to inhibit lithium dendrites, such as the use of electrolyte additives and the construction of artificial SEI membranes, have achieved certain results, it is still difficult to fundamentally balance the uniformity and efficiency of lithium deposition. In this context, exploring new modified diaphragm technologies has become a key way to break through the performance bottleneck of lithium metal batteries. Modified diaphragms introduce special functional materials on their surface or structure, such as polymer coatings, inorganic nanoparticle embedding, or three-dimensional porous structure design, in order to physically block the penetration of lithium dendrites. However, the special functional materials introduced on the surface of the diaphragm block the ion transmission channel during the ion embedding and extraction process, which is not conducive to the transmission of ions. Summary of the invention
[0004] In view of the problems of uncontrollable growth of dendrites and severe interface side reactions in lithium metal negative electrodes in the prior art, a modified diaphragm, a preparation method and a lithium metal battery are provided.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a modified diaphragm, comprising a base film and a modified coating, wherein the modified coating is coated on the surface of the base film, wherein the modified coating comprises a carboxyl precursor and a carbon nanotube composite material, wherein the carboxyl precursor is a precursor modified by a carboxyl modifier, and wherein the precursor comprises GeS or SnS x One of the following, where x=1-2.
[0006] Optionally, in the carboxyl precursor and the carbon nanotube composite material, the mass ratio of the precursor, the carboxyl modified substance and the carbon nanotube is 1:1-20:0.05-1.
[0007] Optionally, the modified coating has a thickness of 0.1-20 μm.
[0008] Optionally, the particle size of the precursor is 0.02-10 μm.
[0009] Optionally, the base film material includes one of a polyethylene base film, a polypropylene base film, a polyethersulfone base film and a polytetrafluoroethylene base film.
[0010] Optionally, the modified coating further includes a binder, and the binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, an acrylic resin, and styrene butadiene rubber.
[0011] Optionally, the carboxyl modifier includes a carboxylated silane coupling agent, and the carboxylated silane coupling agent includes one or more carboxylated derivatives of 3-(trimethoxysilyl)propionic acid, 3-(triethoxysilyl)propionic acid and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0012] Optionally, the method for preparing the modified diaphragm comprises the following operations: S1: Preparation of precursors; S2: mixing the precursor with the carboxyl-modified substance for carboxylation to obtain a carboxylated precursor; S3: ball-milling the carboxyl precursor and the carbon nanotubes to obtain a composite material of the carboxyl precursor and the carbon nanotubes; S4: preparing a slurry of a modified coating by preparing the carboxyl precursor and the carbon nanotube composite material; S5: coating the slurry of the modified coating on the surface of the base film, and obtaining the modified diaphragm after drying.
[0013] Optionally, a dispersant is added during the ball milling process of S3, and the dispersant includes one or more of anhydrous ethanol, acetone, polyvinyl pyrrolidone and sodium dodecyl sulfate.
[0014] Optionally, in S5, the drying temperature is 60-120°C.
[0015] Optionally, the preparation method S1 of the modified diaphragm comprises: The S1 comprises the following steps: mixing a sulfur source with a solvent to obtain a mixed solution; Adding germanium salt or tin salt to the mixed solution, and drying to obtain the precursor.
[0016] Optionally, in S1, the solvent includes one or more of methanol, ethanol, propanol and deionized water.
[0017] Optionally, the sulfur source includes one or more of sodium sulfide, ammonium sulfide, sodium thiosulfate, diethyl sulfide, thiourea and cysteine; and / or, the germanium salt includes one or more of sodium germanate, germanium chloride, potassium germanate, ammonium germanate and tetraethyl germanate; and / or, the tin salt includes one or more of stannous chloride, tin oxide, tin sulfate and tin acetate.
[0018] On the other hand, the present invention provides a lithium metal battery, comprising a positive electrode, a lithium metal negative electrode and the modified diaphragm or a modified diaphragm prepared by the preparation method of the modified diaphragm; The side of the modified separator coated with the modified coating faces the lithium metal negative electrode.
[0019] The beneficial effects of the present invention are: The modified diaphragm provided by the present invention comprises a base film and a modified coating, wherein the modified coating comprises a composite material formed by a carboxyl precursor and carbon nanotubes, the carboxyl functional group in the carboxyl precursor can increase the wettability of the electrolyte, thereby better promoting the infiltration of the electrolyte into the modified diaphragm, and can also interact with lithium ions in the electrolyte to promote lithium ion transmission, and the carboxyl precursor can be in the precursor (GeS or SnS x ) Strong hydrogen bonding is formed between particles, which inhibits the formation of GeS or SnS x The dissociation in the electrolyte makes the GeS or SnS coated on the base film x It is released slowly and gradually during the charge and discharge process of the battery, ensuring that Li-Ge or Li-Sn alloy and a protective SEI film rich in Li2S will always form on the surface of the lithium metal negative electrode, thereby improving the electrochemical performance of the lithium metal negative electrode.
[0020] On the other hand, carbon nanotubes can be well wrapped on the surface of carboxylated precursors. The porous structure of carbon nanotubes can provide additional lithium ion transmission channels, improve ion conductivity, and provide structural support to avoid GeS or SnS x Rapid dissolution in organic electrolyte further enhances the sustainable release characteristics of carboxylated precursors. Carboxyl functional group modification and carbon nanotube composite play a synergistic role in improving GeS or SnS x The ionic conductivity of the coated base film solves the problems of uncontrollable growth of dendrites and interfacial side reactions in the lithium metal negative electrode of the lithium metal battery, and promotes the efficient conduct of the electrochemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the structure of the modified diaphragm provided by the present invention; Figure 2 Schematic diagram of application of the modified diaphragm provided by the present invention in a lithium metal battery; Figure 3 It is a cycle-capacity retention rate curve diagram of the embodiments of the present invention and the comparative example.
[0022] The reference numerals in the drawings of the specification are as follows: 1. Modified coating; 2. Base film; 3. SEI film; 4. Lithium metal anode; 5. Alloy layer. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] In the description of the present invention, it should be understood that the terms "longitudinal", "radial", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0025] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0026] Reference Figure 1 The present invention provides a modified diaphragm, comprising a base film 2 and a modified coating 1, wherein the modified coating 1 is coated on the surface of the base film 2, wherein the modified coating 1 comprises a carboxyl precursor and a carbon nanotube composite material, wherein the carboxyl precursor is a precursor modified by a carboxyl modifier, and wherein the precursor comprises GeS or SnS x One of the following, where x=1-2.
[0027] Specifically, the present invention uses a hydrothermal / solvothermal method to prepare germanium sulfide (GeS2) or tin sulfide (SnS x, x=1-2) precursor, and then the precursor is carboxylated with a carboxyl modifier to obtain a carboxylated precursor (COOH-GeS or COOH-SnS x ), COOH-GeS or COOH-SnS x The carbon nanotube (CNT) is compounded by ball milling, and annealed by calcination in a tube furnace to remove impurities, thereby obtaining carboxylated germanium sulfide / carbon nanotube (COOH-GeS / CNT) or carboxylated tin sulfide / carbon nanotube (COOH-SnSx / CNT).
[0028] Specifically, in the preparation of the germanium sulfide precursor, the amount of germanium salt added accounts for 50%-95% of the precursor; in the preparation of the tin sulfide precursor, the amount of tin salt added accounts for 50%-95% of the precursor.
[0029] In the modified diaphragm provided by the present invention, the carboxyl functional group in the carboxyl precursor can increase the wettability of the electrolyte, thereby better promoting the infiltration of the electrolyte into the modified diaphragm, and can also interact with the lithium ions in the electrolyte to promote the transmission of lithium ions. In addition, the carboxyl precursor can be in the precursor (GeS or SnS x ) Strong hydrogen bonding is formed between particles, which inhibits the formation of GeS or SnS x The dissociation in the electrolyte makes the GeS or SnS coated on the base film 2 x It is released slowly and gradually during the charge and discharge process of the battery, ensuring that a Li-Ge or Li-Sn alloy and a protective SEI film 3 rich in Li2S are always formed on the surface of the lithium metal negative electrode 4, thereby improving the electrochemical performance of the lithium metal negative electrode 4.
[0030] On the other hand, after the carboxylation precursor and carbon nanotubes are ball-milled, the carbon nanotubes can be well wrapped on the surface of the carboxylation precursor. The porous structure of the carbon nanotubes can provide additional lithium ion transmission channels, improve ion conductivity, and provide structural support to avoid GeS or SnS x Rapid dissolution in organic electrolyte further enhances the sustainable release characteristics of carboxylated precursors. Carboxyl functional group modification and carbon nanotube composite play a synergistic role in improving GeS or SnS x The ionic conductivity of the coated base film 2 solves the problems of uncontrollable growth of dendrites and the resulting interface side reactions in the lithium metal negative electrode 4 of the lithium metal battery.
[0031] In some embodiments, in the composite material of the carboxylated precursor and the carbon nanotube, the mass ratio of the precursor, the carboxyl modified substance and the carbon nanotube is 1:1-20:0.05-1.
[0032] Specifically, in the carboxylation precursor and the carbon nanotube composite material, when the carboxylation modifier is too little, the corresponding carboxylation groups on the surface of the modified carboxylation precursor are less, which is not conducive to its function. If the carboxylation modifier is too much, it is not conducive to cost control. Through previous relevant tests, in the modified coating 1, the mass ratio of the carboxylation modifier to other substances is controlled within the above range, which can fully play its role and is also conducive to cost control; if the CNT content is too little, it is not conducive to its function; too much not only has high cost, but also due to the extremely high aspect ratio of CNT, it is difficult to disperse, which is not conducive to performance.
[0033] In some embodiments, the modified coating 1 has a thickness of 0.1-20 μm.
[0034] Specifically, the thickness of the modified coating 1 may be 0.1 μm, 0.5 μm, 1 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm or 20 μm.
[0035] The coating thickness of the modified coating 1 is set within this range, which can ensure that the carboxyl functional groups in the modified coating 1 improve the wettability of the electrolyte and the wettability of GeS or SnS X The particles can be stabilized and release controlled without causing too much hindrance to ion transport due to excessively thick coating. The advantages of the conductive network constructed by CNT and the additional ion transport channels provided can also be better demonstrated. While maintaining good ionic conductivity, the protective effect on the lithium metal negative electrode 4 can also be more fully reflected, so that the electrochemical properties such as battery cycle life and inhibition of dendrite growth can be better optimized.
[0036] In some embodiments, the particle size of the precursor is 0.02-10 μm.
[0037] Specifically, the particle size of the precursor may be 0.02 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 8 μm or 10 μm.
[0038] The particle size of the precursor is within the relatively small particle size range, which means that the unit mass of the precursor has a larger specific surface area. XFor such a precursor, the larger specific surface area enables it to expose more active sites, whether it is to interact with the carboxyl functional group in the carboxyl precursor to form hydrogen bonds, or to react with the electrolyte and the lithium metal negative electrode 4 in the subsequent battery charging and discharging process, the reaction activity will be higher. For example, in terms of forming hydrogen bonds to inhibit its dissociation in the electrolyte, more surface areas can participate in the construction of hydrogen bonds, which can more effectively stabilize its own structure, make it more dispersible in the electrolyte, and be more conducive to releasing it in the expected slow and gradual manner, so as to better act on the surface of the lithium metal negative electrode 4; at the same time, its fine particles can be dispersed more evenly in the modified coating 1, and will not cause obvious blockage to the ion transmission channel. On the contrary, due to its high activity and full contact with the surrounding substances, it helps to optimize the ion transmission environment, cooperate with the carboxyl functional group, etc. to promote lithium ions to pass through the modified coating 1 more smoothly, improve the ionic conductivity of the entire battery system, reduce the polarization phenomenon during the charging and discharging process, and improve the charging and discharging efficiency of the battery.
[0039] In some embodiments, the base film 2 is made of a material selected from the group consisting of a polyethylene base film, a polypropylene base film, a polyethersulfone base film, and a polytetrafluoroethylene base film.
[0040] In some embodiments, the modified coating 1 further comprises a binder, and the binder comprises at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, an acrylic resin, and styrene butadiene rubber.
[0041] In some embodiments, the method for preparing the modified membrane comprises the following operations: S1: Preparation of precursors; S2: mixing the precursor with the carboxyl-modified substance for carboxylation to obtain a carboxylated precursor; S3: ball-milling the carboxyl precursor and the carbon nanotubes to obtain a composite material of the carboxyl precursor and the carbon nanotubes; S4: preparing a slurry of a modified coating by preparing the carboxyl precursor and the carbon nanotube composite material; S5: coating the slurry of the modified coating on the surface of the base film, and obtaining the modified diaphragm after drying.
[0042] Specifically, the preparation method of the modified diaphragm includes the following specific operations: a) fully dissolving a sulfur source in deionized water or other solvent to obtain a mixed solution 1; b) adding germanium salt or tin salt to the mixed solution 1 and fully dispersing the mixture to obtain the mixed solution 2; c) transferring the second mixed solution to a Teflon high-pressure reactor for reaction; d) collecting the precipitate by centrifugation, washing it three times with deionized water and anhydrous ethanol, respectively, and then drying it in an oven overnight to obtain a precursor; e) subjecting the precursor obtained in step d to carboxylation treatment; f) ball milling the carboxylated precursor and CNT; g) The precursor prepared in step f is placed in a tube furnace and annealed at a certain temperature for a certain time in a hydrogen-argon (Ar / 5% vol H2) atmosphere to obtain COOH-GeS / CNT or COOH-SnS x / CNT; h) COOH-GeS / CNT or COOH-SnS x / CNT and polyvinylidene fluoride (PVDF) are mixed in N-methyl-2-pyrrolidone (NMP) solution to prepare COOH-GeS / CNT or COOH-SnSx / CNT slurry; i) COOH-GeS / CNT or COOH-SnS x The / CNT slurry is coated on the base film 2 and dried in an oven overnight to remove the NMP solvent to obtain a modified separator.
[0043] In the present invention, the preparation principle of the modified coating 1 is: using a hydrothermal / solvothermal method, in a sealed reactor, a germanium (Ge) salt or a tin (Sn) salt and a sulfur source are dissolved in water or other solvents, and reacted under high temperature and high pressure conditions to promote the diffusion and crystallization of ions to obtain nano-sized or micron-sized germanium sulfide (GeS2) or tin sulfide (SnS x ) precursor, carboxylating it using a silane coupling agent method to introduce carboxyl functional groups into the precursor; then the carboxyl (-COOH) precursor is crushed, dispersed, refined and compounded with CNT by ball milling. During the ball milling process, the carboxyl (-COOH) precursor and carbon nanotubes are evenly dispersed and tightly combined by mechanical force. The ball milling process also promotes the chemical bonding between the carboxyl precursor and the carbon nanotubes to form a stronger interface bond. Subsequently, it is calcined in a tubular furnace for annealing to remove impurities and obtain COOH-GeS / CNT or COOH-SnS x / CNT Wherein, in step c), the heating temperature is 120-200°C and the insulation time is 6-24 h; In the step g), the heating temperature is 300-800° C., the heating time is 1-12 hours, and the heating rate is 2-10° C. / min; the solvent in a) includes one or more of methanol, ethanol, propanol and deionized water.
[0044] In some embodiments, in step S3, a dispersant is added during the ball milling process, and the dispersant includes one or more of anhydrous ethanol, acetone, polyvinyl pyrrolidone and sodium dodecyl sulfate.
[0045] Specifically, due to the ball milling process, carboxylated precursors such as GeS or SnS X Particles of materials such as carbon nanotubes are prone to aggregate together to form agglomerates due to the interactions between their own surfaces and the van der Waals force between particles. Therefore, dispersants are added during the ball milling process. The dispersants can be adsorbed on the surfaces of these particles and prevent the particles from approaching each other through steric hindrance effects or electrostatic repulsion, thereby effectively avoiding the occurrence of agglomeration.
[0046] In some embodiments, in step S5, the drying temperature is 60-120°C.
[0047] In some embodiments, the carboxyl modifier includes a carboxylated silane coupling agent, and the carboxylated silane coupling agent includes one or more of a carboxylated derivative of 3-(trimethoxysilyl)propionic acid, 3-(triethoxysilyl)propionic acid, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0048] Specifically, the precursor is carboxylated using a silane coupling agent method to introduce carboxyl functional groups into the precursor; on the one hand, the carboxyl group can enhance the wettability of the electrolyte, promote lithium ion transmission, and improve the relevant performance of the electrolyte; on the other hand, it can also react with GeS or SnS X The precursor particles interact with each other, such as forming coordination bonds or hydrogen bonds with some active sites on the surface of the precursor through the carboxyl group, to help stabilize the precursor and control its release process in the electrolyte.
[0049] In some embodiments, the sulfur source includes one or more of sodium sulfide, ammonium sulfide, sodium thiosulfate, diethyl sulfide, thiourea and cysteine; and / or, the germanium salt includes one or more of sodium germanate, germanium chloride, potassium germanate, ammonium germanate and tetraethyl germanate; and / or, the tin salt includes one or more of stannous chloride, tin oxide, tin sulfate and tin acetate.
[0050] Another embodiment of the present invention provides a lithium metal battery, comprising a positive electrode, a lithium metal negative electrode 4 and the modified diaphragm or a modified diaphragm prepared by the preparation method of the modified diaphragm; The side of the modified separator coated with the modified coating 1 faces the lithium metal negative electrode 4 .
[0051] Specifically, refer to Figure 2 The modified separator is coated with the modified coating 1 on one side thereof facing the lithium metal negative electrode 4. When the battery is working, COOH-GeS or COOH-SnS x It will dissociate into Ge in the electrolyte 4+ , S 2- and COOH- or Sn2+ Sn 4+ , S 2- and COOH-, due to G e4+ Sn 2+ Sn 4+ Compared with lithium ion (Li + ) has a higher redox potential, and the free Ge 4+ Sn 2+ Sn 4+ It is easily reduced by the lithium metal on the lithium metal negative electrode to form a Li-Ge or Li-Sn alloy / alloy layer 5 on the lithium metal surface. + The surface energy of Li-Ge or Li-Sn alloys is lower than that of Li metal, making the subsequent Li + Prefers to deposit on Li-Ge or Li-Sn alloys, allowing for uniform Li + flux, inhibiting the growth of lithium dendrites and dissociating S 2- and COOH- can form a stable protective SEI film 3 rich in Li2S on the surface of the lithium metal negative electrode 4, reducing the interface impedance and inhibiting the continuous side reaction between the lithium metal surface and the electrolyte.
[0052] The present invention is further described below by way of examples.
[0053] Example 1 This embodiment is used to illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, and includes the following operations: Add 3g of Na2S to 60ml of deionized water and stir magnetically for 2h, then disperse 2g of Na2GeO3 into the above solution and stir magnetically for 4h until mixed evenly. Transfer the mixed solution to a 100ml Teflon autoclave, keep it in an oven at 150℃ for 15h, and take it out after cooling to room temperature. Collect the precipitate by centrifugation, wash it three times with deionized water and anhydrous ethanol respectively, and then put it in an oven at 80℃ to dry overnight. Dissolve 2g of precipitate and 10.7g of 3-(trimethoxysilyl) propionic acid in 100 deionized water, stir at room temperature for 12h, collect the product by centrifugation, wash it three times with deionized water and anhydrous ethanol respectively, and then dry it in an oven at 80℃ overnight to obtain a carboxylated GeS2 precursor. 2g of carboxylated GeS2 precursor, 1g of CNT and 50ml of anhydrous ethanol were added to a ball mill and milled for 2h for compounding, and then placed in a tube furnace filled with hydrogen and argon atmosphere, and annealed at 500℃ for 4h at a heating rate of 5℃ / min to obtain COOH-GeS / CNT. COOH-GeS / CNT and PVDF were mixed in NMP at a mass ratio of 9:1 to obtain COOH-GeS / CNT modified coating slurry, which was then coated on a 18μm thick PP base film using a 5μm scraper, dried in an oven at 60℃ overnight, and the NMP solvent was removed to obtain a COOH-GeS / CNT coated modified diaphragm.
[0054] LiFePO4 slurry was prepared by mixing lithium iron phosphate (LiFePO4) powder: acetylene black: PVDF in a mass ratio of 8:1:1 in NMP, and then coated on aluminum foil using a 12μm scraper, dried in an oven at 80°C overnight, and then punched into pole pieces with a diameter of 12mm; Lithium metal was used as the negative electrode and LiFePO4 as the positive electrode. The side of the modified diaphragm coated with COOH-GeS / CNT was facing the negative electrode. The lithium metal battery A1 was assembled in a glove box. The electrolyte was 1 mol / L lithium hexafluorophosphate solution, and the solvent of the electrolyte was ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.
[0055] Example 2 This example is used to illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, and includes most of the operations in Example 1, except that: In the preparation of the diaphragm, SnS x (Na2S) precursor to obtain COOH-SnS x / CNT coated modified diaphragm.
[0056] Example 3 This example is used to illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, and includes most of the operations in Example 1, except that: The thickness of the modified coating on the surface of the base film is 0.5 μm.
[0057] Example 4 This example is used to illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, and includes most of the operations in Example 1, except that: The thickness of the modified coating on the surface of the base film is 18 μm.
[0058] Example 5 This example is used to illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, and includes most of the operations in Example 1, except that: In the preparation of the diaphragm, the amount of the carboxyl-modified 3-(trimethoxysilyl)propionic acid added was 5 g.
[0059] Comparative Example 1 This comparative example is used to compare and illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, including most of the operations in Example 1, except that: A commercially available diaphragm was used.
[0060] Comparative Example 2 This comparative example is used to compare and illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, including most of the operations in Example 1, except that: During the preparation of the coating slurry, the precursor was not subjected to carboxyl modification and no carbon nanotubes were added.
[0061] Comparative Example 3 This comparative example is used to compare and illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, including most of the operations in Example 1, except that: No carbon nanotubes were added during the preparation of the coating slurry.
[0062] Comparative Example 4 This comparative example is used to compare and illustrate a modified diaphragm, a preparation method and a lithium metal battery disclosed in the present invention, including most of the operations in Example 1, except that: During the preparation of the coating slurry, the precursor was not subjected to carboxyl modification.
[0063] Performance Testing The lithium metal batteries prepared in the above Examples 1-5 and Comparative Examples 1-4 were electrochemically tested at room temperature. The charge and discharge mode was 0.1C / 0.1C for the first 3 weeks, followed by 1C / 1C charge and discharge for 200 weeks. The voltage range was 2.5V-3.8V, and 1C=150 mA / g.
[0064] The test results obtained are entered in Table 1.
[0065] Under normal temperature 1°C, the cycle number-capacity retention rate of Example 1-2 and Comparative Example 1-2 was tested, and the results were as follows: Figure 3 The cycle number-capacity retention rate curve is given by Figure 3 It can be seen that the cycle performance of Example 1-2 is better than that of Comparative Example 1-2.
[0066] Table 1
[0067] It can be seen from the test results in Table 1 that the test results of the lithium metal batteries prepared in Examples 1-4 in terms of charge specific capacity and cycle performance after charging are better than those in the comparative example; Compared with the test results of Example 1 and Example 2, the charge specific capacity and cycle performance after charging of Example 1 are better than those of Example 2. The reason may be that the conductivity of GeS is usually higher than that of SnS. x During the battery charging and discharging process, GeS can provide lower resistance, reduce energy loss, and improve the overall efficiency of the battery. x The +2 valence state of SnS is not stable enough compared to the +2 valence of GeS. Therefore, when reacting with the carboxylated precursor to construct a composite material, a side reaction may occur due to the valence fluctuation, generating some other tin compound impurities, which are mixed into the composite material system, destroying the uniform and stable structure of the modified coating, resulting in structural defects in the final modified coating, which in turn leads to COOH-SnS x The volume change during dissociation in the electrolyte is greater than that of GeS, which affects the stability of the modified diaphragm after coating. Therefore, in the test results of Example 1 and Example 2, the overall performance of Example 2 is slightly lower than that of Example 1. Compared with Example 1, the coating thickness of Example 3 is too thin, so in the performance test, the test result of Example 3 is worse than that of Example 1; From the test results of Example 4 and Example 1, it can be seen that the test result of Example 4 is significantly lower than that of Example 1. The reason is that the coating thickness of Example 4 is too thick, which is also not conducive to the improvement of performance. Compared with the test results of Example 1 and Example 5, when preparing the modified coating slurry in Example 1, the amount of carboxyl modifier added was slightly higher than that in Example 5. Therefore, compared with the two, the performance of Example 1 in the test was also slightly better than that of Example 5. Compared with the test results of Example 2, the carboxylated precursor and CNT composite play a synergistic role in improving the ionic conductivity of the GeS2 coated base film and maintaining the sustainable release characteristics of COOH-GeS, thereby improving the cycle stability of the lithium metal battery; Compared with the test results of Example 1 and Comparative Example 3, the CNT composite further improves the cycle stability of the lithium metal battery. Compared with Example 1 and Comparative Example 4, the carboxylation characteristics are beneficial to improving the cycle stability of the lithium metal battery; From the performance tests of Comparative Examples 1-4, it can be seen that the test result of Comparative Example 1 is the worst, followed by Comparative Example 2. The reason is that the commercially available diaphragm used in Comparative Example 1 is not coated with a modified coating on its surface, and thus cannot improve the dendrite growth of the lithium metal battery and the problems of interfacial side reactions. In the process of preparing the coating slurry in Comparative Example 2, the precursor is not carboxylated and modified, and CNTs are not added, which is not conducive to the improvement and optimization of battery performance.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified diaphragm, characterized in that: The invention comprises a base film (2) and a modified coating (1), wherein the modified coating (1) is coated on the surface of the base film (2), and the modified coating (1) comprises a composite material formed by a carboxylation precursor and carbon nanotubes, wherein the carboxylation precursor is a precursor modified by a carboxylation modifier, and the precursor comprises GeS or SnS x One of the following, where x=1-2.
2. A modified diaphragm according to claim 1, characterized in that: In the carboxyl precursor and the carbon nanotube composite material, the mass ratio of the precursor, the carboxyl modified substance and the carbon nanotube is 1:1-20:0.05-1.
3. A modified diaphragm according to claim 1, characterized in that: The thickness of the modified coating (1) is 0.1-20 μm.
4. A modified diaphragm according to claim 1, characterized in that: The particle size of the precursor is 0.02-10 μm.
5. The modified diaphragm according to claim 1, characterized in that: The carboxyl modified substance includes a carboxylated silane coupling agent, and the carboxylated silane coupling agent includes one or more of carboxylated derivatives of 3-(trimethoxysilyl)propionic acid, 3-(triethoxysilyl)propionic acid, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
6. A modified diaphragm according to claim 1, characterized in that: The material of the base film (2) includes one of a polyethylene base film, a polypropylene base film, a polyethersulfone base film and a polytetrafluoroethylene base film.
7. The modified diaphragm according to claim 1, characterized in that: The modified coating (1) further comprises a binder, wherein the binder comprises at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, an acrylic resin and styrene butadiene rubber.
8. The method for preparing a modified diaphragm according to any one of claims 1 to 7, characterized in that: The following operations are included: S1: Preparation of precursors; S2: mixing the precursor with the carboxyl-modified substance for carboxylation to obtain a carboxylated precursor; S3: ball-milling the carboxyl precursor and the carbon nanotubes to obtain a composite material of the carboxyl precursor and the carbon nanotubes; S4: preparing a slurry of a modified coating by preparing the carboxyl precursor and the carbon nanotube composite material; S5: coating the slurry of the modified coating on the surface of the base film, and obtaining the modified diaphragm after drying.
9. The method for preparing the modified diaphragm according to claim 8, characterized in that: In S3, a dispersant is added during the ball milling process, and the dispersant includes one or more of anhydrous ethanol, acetone, polyvinyl pyrrolidone and sodium dodecyl sulfate.
10. The method for preparing the modified diaphragm according to claim 8, characterized in that: In S5, the drying temperature is 60-120°C.
11. The method for preparing the modified diaphragm according to claim 8, characterized in that: The S1 comprises the following steps: mixing a sulfur source with a solvent to obtain a mixed solution; Adding germanium salt or tin salt to the mixed solution, and drying to obtain the precursor.
12. The method for preparing the modified diaphragm according to claim 11, characterized in that: In S1, the solvent includes one or more of methanol, ethanol, propanol and deionized water.
13. The method for preparing the modified diaphragm according to claim 11, characterized in that: The sulfur source includes one or more of sodium sulfide, ammonium sulfide, sodium thiosulfate, diethyl sulfide, thiourea and cysteine; and / or, The germanium salt includes one or more of sodium germanate, germanium chloride, potassium germanate, ammonium germanate and tetraethyl germanate; and / or, The tin salt includes one or more of stannous chloride, tin oxide, tin sulfate and tin acetate.
14. A lithium metal battery, characterized in that: Comprising a positive electrode, a lithium metal negative electrode (4) and a modified diaphragm as claimed in any one of claims 1 to 7 or a modified diaphragm prepared by the method for preparing a modified diaphragm as claimed in any one of claims 8 to 13; The side of the modified separator coated with the modified coating faces the lithium metal negative electrode (4).
Citation Information
Patent Citations
Porous diaphragm, preparation method thereof and lithium ion battery
CN111106293A
Functional diaphragm for lithium-sulfur battery and preparation method of functional diaphragm
CN117832755A
Aramid fiber coating slurry, diaphragm as well as preparation method and application of diaphragm
CN118943660A
Nonaqueous electrolyte battery
JP2011141982A
Cited By
Polypyrrole modified diaphragm, preparation method and metal lithium battery
CN122494992A